Framing of Reporting on Alleged Cases of Sexual Harassment at Universitas Riau in Media Cakaplah.com and Riauonline.co.id - Firlia Nouratama (Persepsi: Communication Journal, 2022)
The case of alleged sexual harassment at Universitas Riau emerged on November 4, 2021, after the alleged victim told the chronology through a 13-minute 26-second video. The video was uploaded to the Instagram account @komahi_ur. Cakaplah.com, and Riauonline.co.id were the two media that reported the most cases. Qualitative methods were used in this study using Framing Pan and Kosicki analysis. Later, the framing of the Cakaplah.com and Riauonline.co.id media to see the construction of the reality of an incident related to news of alleged sexual harassment at the Faculty of Social and Political Sciences, Riau University would be discussed. The results showed that the syntactic structure in Cakaplah.com using titles tended to defend the whistleblower. The selection of sources did not lead to an effort to cover both sides, while Riauonline.co.id seemed inclined to support the reported party. In the script structure, Cakaplah.com emphasizes the "how" element, to explain that a complainant is a person who must be protected, while Riauonline.co.id emphasizes the what element, that until there is a court decision the reported person cannot be labelled as a suspect. The thematic structure found that the details used by Cakaplah.com seem to form a bad image of the reported party, while Riauonline.co.id tends to create a good image of the reported party. In rhetoric, the researcher sees Cakaplah.com using words that invite readers' empathy, such as obscenity, being molested, criminal, and others. Meanwhile, Riauonline.co.id chose words that seemed to see this case from the side of the reported person, such as accusations, objections, slander, and others.